(untitled) (The Research of Medical Science Review, 2025)
Background: emergency obstetric hysterectomy (EOH) can save maternal life but it requires proper assessment and adequate surgical skills to avoid complications that may impair quality of life in future. The study results can be helpful to focus on common complications and magnitude of maternal mortality in our setting so that these complications can be prevented. Objective: To determine the frequency of obstetric hysterectomy related complications. Methodology: This descriptive case series study was done at department of OBG, DHQ hospital DG Khan. The study was completed in 6 months [June 2, 2023 till December 2, 2023]. Data of 141 females was collected using non-probability consecutive sampling. Results: The mean age of participants was 33.74 ± 4.40 years, with a range of 16 years (minimum: 24 years, maximum: 40 years). A total of 52(36.9%) of the participants had complications, while 89(63.1%) did not. 14(9.9%) patients experienced in-hospital mortality, 35(24.8%) of the patients developed renal failure, 28(19.9%) suffered bladder injuries, 30(21.3%) had Disseminated Intravascular Coagulation (DIC) while 34(24.1%) of the patients developed a septic wound. Conclusion: Findings indicate that complications are common, with renal failure, bladder injury, disseminated intravascular coagulation, and septic wounds being the most frequently observed adverse outcomes. Maternal age and parity emerged as significant risk factors, with older and multiparous women exhibiting a higher susceptibility to postoperative complications. Additionally, gestational age played a crucial role, as preterm pregnancies were associated with an increased likelihood of infectious complications.